Knockdown of GGCT inhibits cell proliferation and induces late apoptosis in human gastric cancer. Issue 1 (December 2016) - Zhang, Wenjie; Chen, Lei; Xiang, Honggang; Hu, Chunhua; Shi, Weibin; Dong, Ping; Lv, Wenjie
Abstract Background Gamma glutamylcyclotransferase (GGCT) has been proved to be involved in various cancers, but the biological function of GGCT in gastric cancer is still largely unknown. Methods The expression level of GGCT was evaluated by informatics analyses based on the Oncomine database. GGCT gene was then effectively knocked down via lentivirus mediated short hairpin RNA (shRNA) system. Then a series of functional assays, including MTT, colony formation and flow cytometry analysis were conducted on gastric cancer cells following GGCT knockdown. Results We found GGCT is commonly up-regulated in gastric cancer tissues. Furthermore, MTT analysis showed that GGCT depletion significantly inhibited cell proliferation in MGC80-3 and AGS cells. Colony formation assay revealed that depletion of GGCT reduced the colony formation ability in gastric cancer cells. What's more, cell cycle analysis showed that depletion of GGCT induced gastric cancer cell cycle arrested G2/M phase. More importantly, cell apoptosis analysis further revealed that GGCT inhibition induced early and late cell apoptosis in gastric cancer. Conclusion This study suggests GGCT is essential for gastric cancer proliferation and its downregulation may provide a potential anticancer therapy for gastric cancer.